Prevalence of SARS-COV-2 infection and outcomes in Greek sarcoidosis patients - Kotsiou, Ourania; Kirgou, Paraskevi; Tzouvelekis, Argyrios; Kolilekas, Lykourgos; Manali, Effrosyni; Papiris, Spyros; Papakosta, Despina; Antoniou, Katerina; Papanikolaou, Ilias; Steiropoulos, Paschalis; Tomos, Ioannis; Karampitsakos, Theodoros; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: There is limited data on the prevalence of SARS-COV-2 in sarcoidosis patients and the underlying parameters linked to severity. We aimed to conduct a national multicenter study to explore the prevalence of SARS-COV-2 in sarcoidosis patients and investigate its impact on hospitalization and infection rates, describe the characteristics of the infected population and assess the role of these characteristics in determining the likelihood of infection or hospitalization. Methods: We recruited all the adult sarcoidosis patients with who were examined across eight Greek Health Interstitial Lung Disease Referral Centers from the beginning of the pandemic until August 1, 2022. All the data was collected using structured questionnaires. Results: 530 sarcoidosis patients with a mean age of 54±12 years, 60% of whom were females, were recruited. 43% of them were under corticosteroid treatment, and 39% were under additional immunosuppression. 18% of Greek sarcoidosis patients were infected by the virus, which is a lower rate than the general population. The infection was mainly mild. Only one-fifth of the infected sarcoidosis patients required hospitalization, and no deaths or ICU admissions were recorded. Vaccination was found to be associated with a reduced likelihood of infection. Younger age, a longer period since diagnosis, abnormal PET-CT findings, and immunosuppression were associated with an increased probability of infection. Conclusions: The COVID-19 infection rate among Greek sarcoidosis patients was lower than the general population. Fewer than 20% needed hospitalization. There were no deaths or ICU admissions. Vaccination reduces the likelihood of infection. Younger age, longer diagnosis, abnormal PET-CT findings, and immunosuppression increased the chance of infection.